THE DEVELOPMENT OF ISLAMIC CIVILIZATION FROM PRE-ISLAMIC TO MODERN TIMES IN THE ARCHIPELAGO - Siti Muhibah; Aslan Aslan (Adisam Publisher, 2025)
The development of Islamic civilization in the archipelago has deep roots, starting from the pre-Islamic period to the modern era, bringing significant transformations in various aspects of community life. The process of Islamization that took place through trade interactions and the spread of Islamic scholars has incorporated Islamic values that adapt to local wisdom, enriching local social, cultural and political traditions. The presence of Islamic kingdoms attests to the integration of Islamic teachings in governmental and societal structures, while the contribution of art, law and education also created a unique synergy that endures to this day. In modern times, the influence of Islam is increasingly rooted in the fabric of society through the work of Islamic organizations that strengthen the education, economic and social sectors, thus reflecting a sustainable contribution in building an inclusive and tolerant national identity.